2009
DOI: 10.1007/s00167-009-0794-0
|View full text |Cite
|
Sign up to set email alerts
|

Popliteofibular ligament reconstruction for posterolateral external rotation instability of the knee

Abstract: The aim of this study was to assess the clinical outcome of popliteofibular ligament (PFL) reconstruction for posterolateral external rotation instability of the knee. PFL reconstruction was performed consecutively in 22 patients with chronic external rotation instability of the knee. The inclusion criterion for surgery was tibial external rotation of 10 degrees more than the contralateral uninjured knee without varus laxity. A double bone tunnel was created at the PFL insertion of the fibular head through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…Our finding about the length of LCL was similar to previous studies, as shown in Table II (Maynard et al, 1996;Ishigooka et al, 2004;Espregueira-Mendes & da Silva;Zhang et al, 2009;Jung et al;Osti et al). In most of the cases, LCL was wider at the upper part and narrower at the lower part, in accordance with the findings of Takeda et al In these literatures, width of LCL was given from the midportion or at the level of articular line.…”
Section: Lateral (Fibular) Collateral Ligamentsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding about the length of LCL was similar to previous studies, as shown in Table II (Maynard et al, 1996;Ishigooka et al, 2004;Espregueira-Mendes & da Silva;Zhang et al, 2009;Jung et al;Osti et al). In most of the cases, LCL was wider at the upper part and narrower at the lower part, in accordance with the findings of Takeda et al In these literatures, width of LCL was given from the midportion or at the level of articular line.…”
Section: Lateral (Fibular) Collateral Ligamentsupporting
confidence: 91%
“…It was stated that PT attached 0.84-18.5 mm anterior to the LCL (Bartonícek, 2005;Brinkman et al;Kim et al). In some other studies, PT has been expressed to locate in three positions: posteroinferior, just inferior or posterior to the LCL in extension position of the knee (Ullrich et al, 2002;Zhang et al;Jung et al). Additionally, in the study of Zeng et al, it was stated that PT was overlapped by LCL.…”
Section: Lateral (Fibular) Collateral Ligamentmentioning
confidence: 99%
“…Many surgical methods recommend a tunnel anteroinferior to the LCL attachment on the femur condyle (Nau et al 2005;Zhang et al 2009;LaPrade et al 2003LaPrade et al , 2010. Whereas, according to research by Jung et al (2010) and Yang et al (2011), if the original site of the PT cannot be seen, a posteroinferior site femoral tunnel, as with the LCL attachment, is recommended.…”
Section: The Popliteus Tendon and Its Clinical Implicationsmentioning
confidence: 97%
“…Despite its important clinical significance, PLS injuries are still frequently undiagnosed and left untreated clinically due to its complex structures and variations in anatomy (Covey 2001;LaPrade et al 2003;Nau et al 2005;Zhang et al 2009). The structures of the PLS can be divided into two primary components: the lateral collateral ligament (LCL) and the popliteus complex (PC; Ullrich et al 2002;Zantop et al 2007;Gadikota et al 2010;Jung et al 2010;Yang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…53 Surgical reconstruction of a disrupted popliteofibular ligament has been found to be beneficial in patients with posterolateral external rotatory instability of the knee. 65 …”
Section: 62mentioning
confidence: 99%